Analisis Rasio Arus Kas Untuk Mengukur Kinerja Keuangan Pada Pt Indofood Sukses Makmur Tbk. Periode 2018-2020 - Febryanti Febryanti; Syntha Noviyana (Ridwan Institute, 2022)
The purpose of this study was to determine and analyze the financial performance as measured by the cash flow ratio at PT. Indofood Sukses Makmur Tbk. 2018-2020 period. This study uses the following cash flow ratio analysis methods: operating cash flow ratio (AKO), fund flow coverage ratio (CAD), cash to interest coverage ratio (CKB), cash to current debt coverage ratio (CKHL), capital expenditure ratio ( PM), total debt ratio (TH). The type of data used in this research is quantitative data. Sources of data used in this study is secondary data. In the form of a Financial Statement consisting of a Balance Sheet, Income Statement and Cash Flow Statement at PT. Indofood Sukses Makmur Tbk period 2018-2020. The data collection technique used in this study to obtain the data and information needed is a documentation study, namely through the website of the Indonesia Stock Exchange (www.idx.co.id). The author uses quantitative analysis techniques, namely calculating and analyzing the relevant results from the financial statements, using the cash flow statement ratio. The results of the study note that the financial performance of PT. Indofood Sukses Makmur Tbk for the 2018-2020 period shows that there are three cash flow ratios whose values ​​are still below the applicable standard criteria because the company has not been able to meet current obligations and long-term debt on time but the company can cover interest costs, capital expenditures, and is able to pay taxes. of the cash flow generated by the company.